Postcards from Qatar: Introduction (Papers from the Institute of Archaeology, 2017)
This report is the first of a series of ‘Postcards from Qatar’ aimed at providing information and updates on projects conducted by UCL Qatar in the region by both staff and students. This initial postcard provides an overview of UCL Qatar courses and facilities, an account of campus life, as well as a review of an exhibition for Doha’s Msheireb Museum created by the museum studies masters students.